Respuesta :

Answer:

d

Step-by-step explanation:

[tex]x 1= \frac{ - b + \sqrt{ {b}^{2} - 4ac} }{2a} \\ x2 = \frac{ - b - \sqrt{ {b}^{2} - 4ac} }{2a} \\ x1 = \frac{ - 2 + \sqrt{ {2}^{2} - 4\times 1 \times ( - 3)} }{2} = 1 \\ x2 = \frac{ - 2 - \sqrt{ {2}^{2} - 4 \times 1 \times ( - 3)} }{2} = - 3[/tex]

Answer:

d

Step-by-step explanation:

Solving by factorising

Given

x² + 2x - 3 = 0 ← in standard form

(x + 3)(x - 1) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 3 = 0 ⇒ x = - 3

x - 1 = 0 ⇒ x = 1